2020
DOI: 10.3390/ijerph17020401
|View full text |Cite
|
Sign up to set email alerts
|

Endometriosis and Pregnancy: A Single Institution Experience

Abstract: Endometriosis may compromise the physiological course of pregnancy. The aim of this prospective observational study was to evaluate whether endometriosis causes a higher prevalence of obstetric and neonatal complications as well as a higher risk of caesarean section and to detect a possible correlation between the presence, type, and location of endometriosis and obstetric complications, previous surgery, and pregnancy outcome, as well as the influence of pregnancy on the course of the disease. We compared two… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
36
0
3

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(54 citation statements)
references
References 47 publications
(73 reference statements)
5
36
0
3
Order By: Relevance
“…Moreover, the authors observed higher incidence of placenta previa in the study group (1.6% vs 0%), but the result did not reach significance. These conclusions are concordant with the findings of previous researchers (reported OR 2.0-3.99 for placental abruption and 3.9-15.1 for placenta previa) [13,15,20,21].…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…Moreover, the authors observed higher incidence of placenta previa in the study group (1.6% vs 0%), but the result did not reach significance. These conclusions are concordant with the findings of previous researchers (reported OR 2.0-3.99 for placental abruption and 3.9-15.1 for placenta previa) [13,15,20,21].…”
Section: Discussionsupporting
confidence: 93%
“…According to our results, endometriosis seems to be positively correlated with the incidence of elective caesarean sections (OR = 1.8). This finding is concordant with previous studies (Porpora et al, Horton et al) [21,22]. Nevertheless, vaginal labor does not increase the risk of peritoneal injuries among women who underwent surgery for deep infiltrating endometriosis and may reduce the recurrence of endometriosis symptoms after delivery [23,24].…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Heterogeneity was high (I 2 = 94%). Neither the secondary analysis including all studies regardless of study quality not the sub-analysis including only spontaneous pregnancies [45,48,52,57] changed the direction of the association between endometriosis and cesarean section (Supplementary Figure S17). The funnel plot was rather symmetrical (Supplementary Figure S18).…”
Section: Cesarean Sectionmentioning
confidence: 99%
“…the number of pregnancies was not reported (5). More recent case series of pregnant women with endometriosis suggest that this risk may be very low but the relatively small number of included cases or the study designs hamper a precise estimate of the risk (6)(7)(8).…”
Section: Introductionmentioning
confidence: 99%